2007
DOI: 10.1016/j.cmet.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Role for Phosphatidylinositol 3-Kinase but Not Akt Signaling in Mitochondrial Adaptations that Accompany Physiological Cardiac Hypertrophy

Abstract: Physiological cardiac hypertrophy is associated with mitochondrial adaptations that are characterized by activation of PGC-1alpha and increased fatty acid oxidative (FAO) capacity. It is widely accepted that phosphatidylinositol 3-kinase (PI3K) signaling to Akt1 is required for physiological cardiac growth. However, the signaling pathways that coordinate physiological hypertrophy and metabolic remodeling are incompletely understood. We show here that activation of PI3K is sufficient to increase myocardial FAO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
118
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 47 publications
(63 reference statements)
10
118
0
Order By: Relevance
“…In thinking about candidate proteins downstream of PI3K, other than Akt and TOR, we noted that PKC and  had recently been shown to be required for changes in mitochondrial metabolism in the heart following exercise (O'Neill et al, 2007). There are important differences between this system and the effect of NRG and IGF on mitochondria biogenesis, in that in the study by O'Neill and colleagues increased mitochondrial function was not accompanied by changes in mitochondria amount or mtDNA copy number.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In thinking about candidate proteins downstream of PI3K, other than Akt and TOR, we noted that PKC and  had recently been shown to be required for changes in mitochondrial metabolism in the heart following exercise (O'Neill et al, 2007). There are important differences between this system and the effect of NRG and IGF on mitochondria biogenesis, in that in the study by O'Neill and colleagues increased mitochondrial function was not accompanied by changes in mitochondria amount or mtDNA copy number.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent report, it was shown that the increase in fatty acid oxidation and TCA-cycle activity following exercise-induced cardiac hypertrophy in mice is dependent on PI3K, independent of TOR and dependent on PKC and PKC (O'Neill et al, 2007). We therefore investigated whether PKC is involved in the increase in mitochondrial gene expression stimulated by NRG+IGF.…”
Section: Nrg and Igf Cooperate To Affect Mitochondrial Gene Expressionmentioning
confidence: 99%
“…UCP3 can protect muscle cells against mitochondrial ROS and oxidative damage [30], and overexpression of Tfam protected the heart against mitochondrial respiratory defects and cardiac dysfunction in a setting of myocardial infarction [36]. In addition, it was previously shown that isolated mitochondria from caPI3K mice (basal conditions) had increased mitochondrial enzymatic activity, associated with increased fatty acid oxidative capacity [37].…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54] PI3K(p110␣) has also been reported to differentially regulate metabolism genes in ventricular tissue. 55 Further studies are required to examine the functional consequence of these alterations in gene expression.…”
Section: Discussionmentioning
confidence: 99%